Study of Machining Time in Drilling process using Ant Colony Algorithm and CAM software - abdullah, haslina (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Optimization of machining time in the CNC machining process is important for improving the productivity of the machining process. In this present study, a non-conventional method called Ant Colony Optimisation (ACO) was applied in order to reduce the amount of time required for the machining process by shortening the length of the tool path taken during the drilling process. The workpiece that had 36 holes was designed in the SolidWorks software in order to study the overall length of the tool path based on the drilling process. Matlab software was used to develop an ACO algorithm to figure out the best length for the tool path in drilling. The model was then transferred to Mastercam software for tool path simulation in order to compare the tool path length and machining time between the ACO approach and the default Mastercam method. There are five types of drilling tool path has been implemented in Mastercam. The ACO results show that the optimization procedure can shorten the tool path length in the drilling process with a percentage difference of 8% when compared to the machining time generated by Mastercam software.